Bio Art in the Art World - Szykowna, Sylwia (Sensus Historiae, 2020)
Art from the area of art&science has long since reached the age of maturity, from the 1960s, functioning in the margins of the world of contemporary art in the world of new media art. This article looks at this situation, looking for the reasons for this discrepancy, resulting in low visibility of the actions taken. The author focuses her attention on biological art, growing out of the experience of the art of new media, which is quite a challenge for existing institutional practices in the field of exhibition, conservation and protection of works whose medium is life in its purely biological and not just metaphorical dimension.